# Solve using the Square Root Property 2x^2-3x-11=0 2×2-3x-11=0
Use the quadratic formula to find the solutions.
-b±b2-4(ac)2a
Substitute the values a=2, b=-3, and c=-11 into the quadratic formula and solve for x.
3±(-3)2-4⋅(2⋅-11)2⋅2
Simplify.
Simplify the numerator.
Raise -3 to the power of 2.
x=3±9-4⋅(2⋅-11)2⋅2
Multiply 2 by -11.
x=3±9-4⋅-222⋅2
Multiply -4 by -22.
x=3±9+882⋅2
Add 9 and 88.
x=3±972⋅2
x=3±972⋅2
Multiply 2 by 2.
x=3±974
x=3±974
Simplify the expression to solve for the + portion of the ±.
Simplify the numerator.
Raise -3 to the power of 2.
x=3±9-4⋅(2⋅-11)2⋅2
Multiply 2 by -11.
x=3±9-4⋅-222⋅2
Multiply -4 by -22.
x=3±9+882⋅2
Add 9 and 88.
x=3±972⋅2
x=3±972⋅2
Multiply 2 by 2.
x=3±974
Change the ± to +.
x=3+974
x=3+974
Simplify the expression to solve for the – portion of the ±.
Simplify the numerator.
Raise -3 to the power of 2.
x=3±9-4⋅(2⋅-11)2⋅2
Multiply 2 by -11.
x=3±9-4⋅-222⋅2
Multiply -4 by -22.
x=3±9+882⋅2
Add 9 and 88.
x=3±972⋅2
x=3±972⋅2
Multiply 2 by 2.
x=3±974
Change the ± to -.
x=3-974
x=3-974
The final answer is the combination of both solutions.
x=3+974,3-974
The result can be shown in multiple forms.
Exact Form:
x=3+974,3-974
Decimal Form:
x=3.21221445…,-1.71221445…
Solve using the Square Root Property 2x^2-3x-11=0   ## Download our App from the store

### Create a High Performed UI/UX Design from a Silicon Valley.  Scroll to top